Módulos efêmeros para as feiras itinerantes da zona sul da cidade de Manaus - Freitas, Lucas Costa Drago de (Brasil, 2023)
This Final Graduation Work 2 aims to address the theme of Ephemeral Modules for Feiras Prefeito 1, providing an in-depth analysis of the day-to-day, history, assembly, disassembly and implementation of these temporary structures. The main focus is the development of efficient solutions for the Prefeito 1 Traveling Fairs, located in the south zone of the city of Manaus, Amazonas. In the current context, it is crucial to consider the precariousness of fair spaces and the challenges faced in relation to unhealthy conditions and inadequate conditions. Faced with these issues, the central proposal of this study is the design of ephemeral modules that can meet the demands and improve conditions for merchants, visitors and the entire community involved. The elaboration of ephemeral modules implies a multidisciplinary approach, combining knowledge of architecture, design, engineering and urbanism. Through a detailed research process, the main needs and challenges faced by fairs will be identified, as well as the specific characteristics of the local context. The implementation of ephemeral modules requires a thorough analysis of the areas available at Prefeito 1 fairs, considering aspects such as accessibility, spatial distribution, existing infrastructure and functional demands. Adapting these temporary structures to the urban environment is essential to ensure smooth and efficient integration with the city. In addition, factors such as sustainability and energy efficiency will be considered in the design of ephemeral modules. The use of ecologically responsible materials and technologies, combined with reuse and resource saving strategies, will contribute to a more sustainable approach with less environmental impact. Finally, the study seeks to contribute not only to the improvement of the Prefeito 1 fairs in terms of infrastructure and working conditions, but also to the strengthening of local commerce and the promotion of the regional economy. The creation of suitable and attractive spaces will be able to attract a greater number of visitors, boost the development of enterprises and generate a positive impact on the lives of the stallholders and on the community as a whole. In this way, the research on the Ephemeral Modules for the Prefeito 1 Fairs presents itself as a relevant and current theme, which aims to propose innovative and sustainable solutions to improve the conditions of the traveling fairs, promoting economic growth and the valorization of the urban spaces used for these events.